2000
DOI: 10.1016/s0169-5983(00)00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the turbulent boundary layer flow over riblets surface

Abstract: The laser Doppler velocimeter (LDV) and hydrogen bubble ow visualization techniques have been used to measure the characteristics of turbulent boundary layer ow over riblets surface and to observe its coherent structure in the near wall region. The experimental results indicate that, in comparison with the turbulent boundary layer ow over a smooth surface, greater values are obtained for the thickness of viscous sublayer, the thickness of bu er region and the integral constant C in the log-law. Moreover, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…All the data presented in Figs4, 5, 6 and7 at each position (x), indicate that the logarithm laws AlogY + +B, for the smooth case is different from the one for the L-shaped riblets. The same behavior was well confirmed by Wang, Lan and Chen, 2000 [18] and by Brima, Atmani and Achour, 2006 [19] for the V-riblets surfaces. The theoretical shear stress values for smooth and riblets surfaces are given in Tables 1 and 2 Tables 1 and 2; we can observe that the ribbed surface boundary layer thickness is thinner than that of the smooth one.…”
Section: Theoretical Approachsupporting
confidence: 81%
“…All the data presented in Figs4, 5, 6 and7 at each position (x), indicate that the logarithm laws AlogY + +B, for the smooth case is different from the one for the L-shaped riblets. The same behavior was well confirmed by Wang, Lan and Chen, 2000 [18] and by Brima, Atmani and Achour, 2006 [19] for the V-riblets surfaces. The theoretical shear stress values for smooth and riblets surfaces are given in Tables 1 and 2 Tables 1 and 2; we can observe that the ribbed surface boundary layer thickness is thinner than that of the smooth one.…”
Section: Theoretical Approachsupporting
confidence: 81%
“…Skin friction drag shares a very quotient in the total drag, even over 60% or 80% for the streamlined bodies and 100% for pipe transportation [3,4]. Therefore, skin friction drag reduction is a key for drag reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.5 shows that there are nearly double streaks on the smooth surface than on the groove surface. This conclusion is oppositive with the result in [6]. Wang et alE61 found that the average spacing between the neighbour streaks was shorter on one kind of groove surface.…”
Section: Flow Structures In the Sublayermentioning
confidence: 79%